Perturbation Analysis of the Algebraic Metric Generalized Inverse in Lp(Ω, μ). (2nd December 2017) - Cao, Jianbing; Xue, Yifeng
ABSTRACT: Let X = L p (Ω, μ ) (1< p <∞) and T, δT : X → X be bounded linear operators. Put . In this paper, using the notion of quasi-additivity and the concept of stable perturbation, we will give some estimates of the upper bound of in terms of the gap function. As an application of main results, we also investigate the best approximate solution problem of ill-posed operator equation.